Prinsip Free, Prior, and Informed Consent dalam Mencegah Deforestasi di Hutan Adat - Nuryasinta, Radhityas Kharisma; Cholidah, Cholidah (Fakultas Hukum Universitas Hang Tuah, 2025)
Free, Prior, and Informed Consent (FPIC) is an International legal standard that guarantees indigenous peoples' right to consent to projects affecting their territories and lives. Indonesia has not explicitly adopted this principle in its national legal system, so the management of customary forest areas. The absence of clear FPIC regulations creates legal loopholes impacting the legitimacy of business licenses and the protection of indigenous peoples' rights, which can lead to human rights violations. This study aims to analyze how FPIC is regulated and implemented in Indonesian national law, as well as assess the legal consequences of noncompliance in the context of customary forest management. Using normative legal research methods and statutory and conceptual approaches, the study concludes that disregarding FPIC not only goes against the spirit of the constitution and international commitments but also contributes to social disintegration and unequal power relations between indigenous peoples and the state. Therefore, the principle of FPIC must be explicitly recognized in national laws and regulations, and participatory, fair, and legally binding implementation mechanisms must be established to realize inclusive and ecologically just development.